Numerical modeling of unsaturated layered soil for rainfall-induced shallow landslides - Liu, Chih-Yu; Ku, Cheng-Yu; Xiao, Jing-En; Huang, Chi-Chao; Hsu, Shih-Meng (Journal of Environmental Engineering and Landscape Management, 2017)
In this paper, a pioneer study on numerical modeling of rainfall-induced shallow landslides in unsaturated layered soil using the variably saturated flow equation is presented. To model the shallow landslides, the infinite slope stability analysis coupled with the hydrological model with the consideration of the fluctuation of time-dependent pore water pressure and Gardner equation for soil water characteristic curve was developed. A linearization process for the nonlinear Richards equation to deal with groundwater flow in unsaturated layered soil is derived using the Gardner model. To solve one-dimensional flow in the unsaturated zone of layered soil profiles, flux conservation and the continuity of pressure potential at the interface between two consecutive layers are considered in the numerical discretization of the finite difference method. The validity of the proposed model is established in three numerical problems by comparing the results with the analytical and other numerical solutions. Application examples have also been conducted. Obtained results demonstrate that the fluctuation of pore water pressure in unsaturated layered soil dominates slope stability of landslides and the lowest factor of safety may occur at the interface between two consecutive layers. The findings observed in this study are a fundamental contribution to environmental protection engineering for landslides in areas with higher occurrence and vulnerability to extreme precipitation.